A typology of research designs in qualitative research - Christodoulou, Michalis (The Greek Review of Social Research, 2022)
In this article we argue that causal knowledge constitutes the epistemological knowledge claim which differentiates case studies research designs from biographical, narrative and ethnographic research designs in which different knowledge claims are produced. By drawing upon the social ontology of Critical Realism, we propose the idea that causal knowledge is tied up with typological theorizing and relational mechanisms. We develop a typology of case studies research designs according to whether or not theory covers conditions or outcomes related to the phenomenon of interest, and from which (theory) specific kinds of case selection are implemented. We provide detailed accounts on the reasons why case studies are a powerful methodological tool for theory development and for producing causal explanations.